2011
DOI: 10.1016/j.cct.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Are propensity scores really superior to standard multivariable analysis?

Abstract: Clinicians often face difficult decisions despite the lack of evidence from randomized trials. Thus, clinical evidence is often shaped by non-randomized studies exploiting multivariable approaches to limit the extent of confounding. Since their introduction, propensity scores have been used more and more frequently to estimate relevant clinical effects adjusting for established confounders, especially in small datasets. However, debate persists on their real usefulness in comparison to standard multivariable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
152
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 205 publications
(157 citation statements)
references
References 50 publications
(53 reference statements)
2
152
0
3
Order By: Relevance
“…Our review identified a total of nine studies: eight studies 62-69 compared the results of regression analysis, instrumental variables and propensity scoring and a further study 70 discussed the relative merits of the alternative methods of adjustment. Two of these studies were systematic reviews: Shah et al 66 reviewed comparisons between propensity scoring and regression methods and Shah et al 66 and Laborde-Castérot et al 69 reviewed comparisons between propensity scoring and instrumental variable analyses.…”
Section: Effectiveness Of Adjustment Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our review identified a total of nine studies: eight studies 62-69 compared the results of regression analysis, instrumental variables and propensity scoring and a further study 70 discussed the relative merits of the alternative methods of adjustment. Two of these studies were systematic reviews: Shah et al 66 reviewed comparisons between propensity scoring and regression methods and Shah et al 66 and Laborde-Castérot et al 69 reviewed comparisons between propensity scoring and instrumental variable analyses.…”
Section: Effectiveness Of Adjustment Methodsmentioning
confidence: 99%
“…Biondi-Zoccai et al 70 concluded that there is no clearly superior method, noting that 'both standard multivariable methods and propensity scores have key limitations, and none is able to take into account unknown confounders' (p. 736). Biondi-Zoccai et al, 70 however, go on to suggest that propensity scoring methods may have advantages over regression methods when the sample size is small and that, although instrumental variables methods are not without their limitations, they are the only methods that allow for unobserved confounding to be adjusted for.…”
Section: Propensity Scoring Compared With Instrumental Variables Analmentioning
confidence: 99%
See 3 more Smart Citations